2012
DOI: 10.1289/ehp.1103667
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in Oxidative Potential and Other Particulate Matter Characteristics Collected Near Major Streets and Background Locations

Abstract: Background: Measuring the oxidative potential of airborne particulate matter (PM) may provide a more health-based exposure measure by integrating various biologically relevant properties of PM into a single predictor of biological activity.Objectives: We aimed to assess the contrast in oxidative potential of PM collected at major urban streets and background locations, the associaton of oxidative potential with other PM characteristics, and the oxidative potential in different PM size fractions.Methods: Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
61
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 29 publications
14
61
2
Order By: Relevance
“…These results can be explained by the specificity of the ESR assay towards hydroxyl radical generation and in the case of Ba (not redox-active) linked to its co emission with the former redox active compounds. These results agree with the study of Boogaard et al (2012) where the OP ESRv of PM collected near major urban road were highly correlated with Cr, Cu and Ba. However, OP ESRv is also 15 associated to organic compounds (OC, PAH) in other studies .…”
Section: Univariate Data Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…These results can be explained by the specificity of the ESR assay towards hydroxyl radical generation and in the case of Ba (not redox-active) linked to its co emission with the former redox active compounds. These results agree with the study of Boogaard et al (2012) where the OP ESRv of PM collected near major urban road were highly correlated with Cr, Cu and Ba. However, OP ESRv is also 15 associated to organic compounds (OC, PAH) in other studies .…”
Section: Univariate Data Analysessupporting
confidence: 92%
“…DTT is known to react with organic compounds but also with transition metals (Charrier and Anastasio, 2012;Lin and Yu, 2011). The ESR assay employs the spin trap 5,5-Dimethyl-1-pyrroline N-oxide (DMPO) and is specific for reactive radical species, which for example result from partial reduction of dioxygen catalyzed by transition metal (Boogaard et al, 2012;Shi et al, 2003). The AA assays would be more 30 specific to the oxidative potential of transition metals (Godri et al, 2011;, but ascorbic acid is known to react with organics such as quinones (Shang et al, 2012;Visentin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soto et al (2008) reported the cytotoxicity of BC in commercial nanoparticle materials. Boogaard et al (2012) observed an association between PM oxidative potential and soot carbon in ambient aerosol collected in traffic areas. Harder et al (2005) reported the effect of BC on heart-rate increase but no inflammatory effects, while Cho et al (2005) observed a correlation between ambient soot carbon and PM oxidative potential.…”
Section: Particulate Matter and Healthmentioning
confidence: 91%
“…Its possible importance for health is currently being discussed (Shiraiwa, Selzle & Pöschl, 2012). Initial studies on spatial and temporal variations of particle reactivity parameters have been conducted (Boogaard et al, 2012a;Künzli et al, 2006). Still missing is the link between particle reactivity and other particle characteristics, the actual mechanisms triggered, and the ageing and/or changes of particle reactivity during atmospheric transport due to chemical reactions.…”
Section: Changing Reactivity Over Time or With Increasing Distance Frmentioning
confidence: 99%